A fuzzy based MCDM methodology for risk evaluation of cyber security technologies - Erdogan, Melike; Karasan, Ali; Kaya, İhsan; Budak, Ayşenur; Çolak, Murat (Springer Verlag service@springer.de, 2020)
Cyber security that also known as information technology security is to protect computers, mobile devices, servers, electronic systems and networks from malicious digital attacks. In recent years, cyber security threats have been a growing problem for any critical digital infrastructure and various cyber-attacks created over the Internet are also becoming a big issue for the society. Therefore, the use of technologies developed to provide cyber security is very important. However, the risks of cyber security technologies should be taken into account when choosing among cyber security technologies. For this aim, we have proposed a multi-criteria decision making (MCDM) methodology based on hesitant fuzzy sets (HFSs) that gives experts extra flexibility in using linguistic terms to evaluate the criteria and alternatives to determine the best cyber security technology. For this aim, a study has also been discussed which deals with risk factors in the selection of cyber security technologies via fuzzy MCDM process. © 2019 Elsevier B.V., All rights reserved.
International Conference on Intelligent and Fuzzy Systems, INFUS 2019 -- Istanbul -- 228529
Keywords: Cyber security technology; Hesitant fuzzy sets; Multi criteria decision making; Risk evaluation